An Estimation of the Taxable Capacity, Tax Effort and Tax Burden of an Emerging Economy: Evidence from Ghana - Amoh, John Kwaku (International Journal of Economics and Financial Issues, 2019)
This paper estimates taxable capacity, tax effort and tax burden with a view to examining the tax fairness perceptions and tax system efficiency. The study employed ordinary least squares (OLS) regression and vector autoregressive (VAR) model for historical time series data sourced from the World Development Indicators (WDI) and Bank of Ghana (BoG). We found that Ghana’s overall tax burden and average post-tax reform efforts are low suggesting tax fairness and tax system inefficiency respectively. We conclude that post-tax reform dispensation has not generated the much-needed tax revenues because of low tax efforts. Thus, tax revenue could be significantly maximized to aid the achievement of the sustainable development goals (SDGs) to move Ghana Beyond Aid. This paper extends literature by relying on estimates of taxable capacity, tax effort and tax burden to assess the tax fairness perceptions and tax administrative efficiency of an emerging economy. We posit that these triad terminologies move pari passu in assessing the efficiency and fairness of a country’s tax system. We recommend that embarking on jurisdictional tax reforms should not only be about appropriate and a plethora of tax laws and multiplicity of taxes but also on the efficiency and integrity of tax administration. The judicious use and prompt accountability of tax revenues could help address tax unfairness perceptions in emerging economies. Keywords: Taxable capacity, tax effort, tax burden, fairness, Ghana, tax revenue JEL Classifications: H2, Q2, Q3 DOI: https://doi.org/10.32479/ijefi.7549